PENGOLAHAN SAMBAL IKAN TUNA SEBAGAI IMPLEMENTASI KULIAH KERJA NYATA DALAM PEMBERDAYAAN MASYARAKAT DESA PINOMONTIGA - Bakari, Yuliana; Nento, Wila Rumina; Wibowo, Larasati Sukmadewi; Samatowa, Lukman (Universitas Negeri Gorontalo, 2023)
Thematic KKN in Pinomontiga village, Bone Bolango Regency, Bulawa District, is innovating to make tuna fish sauce products and providing education to the people of Pinomontiga village regarding the process of processing tuna fish sauce and how to market strategies for tuna fish sauce products.The activity of making tuna fish sauce products was carried out on Monday (28/8/2023), in the Pinomintiga Village Office Hall with the theme